Pemikiran Politik Islam Di Indonesia: Dari Formalistik Menuju Ke Substantif - Rachmat Panca Putera (Ri'ayah: Jurnal Sosial dan Keagamaan, 2018)
Political thinking about the relationship religion and countries have a problem with the most attractive to moslem community, the relationship between islam and state in indonesia in be indonesian history is a story antagonistic and suspicion each other.Not intimate relationship is mainly, but not wholly , caused by the views on the founder of the country most of it muslims about was about to be taken kemanakah country newly independent.One of the most important items in a difference of opinion on wased this country inclined to islam , or nationalist muslim religion not determinant certain system for muslims.Political islam in indonesia can not be separated from the dynamics of thought and the renewal of a movement .Among in general divided into two groups .The first group were convinced that the islamic state of as a model of government will guarantee the teachings of islam implemented in the community .The second group refuse formalism religion in state affairs , the opposite of them focused on the importance of grow and to create and integrity of the religious society of the people.